2022
DOI: 10.1530/edm-21-0035
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin-associated severe hyponatremia: a rare and potentially adverse effect?

Abstract: Summary Sodium-glucose cotransporter-2 inhibitors (SGLT2i) induce osmotic diuresis by inhibiting the proximal renal tubular reabsorption of the filtered glucose load, which in turn can occasionally lead to severe dehydration and hypotension amidst other adverse effects. We present a case of a 49-year-old man with type 2 diabetes mellitus (T2D) on canagliflozin, a SGLT2i. The patient was brought to the emergency room following a motor vehicle accident. He was confused and had an altered mental status. His blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“… 2 However, a real world study showed that 38.6% patients who took SGLT2i suffered side effects, 3 including urinary tract infection, non-hyperglycemic ketoacidosis, hyponatremia, and higher risk of amputation. 4 , 5 , 6 , 7 Therefore, although ACEI/ARB and SGLT2i can delay the progression of DKD, the side effects affect their application. Safer and more efficient treatments are needed.…”
Section: Introductionmentioning
confidence: 99%
“… 2 However, a real world study showed that 38.6% patients who took SGLT2i suffered side effects, 3 including urinary tract infection, non-hyperglycemic ketoacidosis, hyponatremia, and higher risk of amputation. 4 , 5 , 6 , 7 Therefore, although ACEI/ARB and SGLT2i can delay the progression of DKD, the side effects affect their application. Safer and more efficient treatments are needed.…”
Section: Introductionmentioning
confidence: 99%